Sweet land [videorecording (DVD)] - Selim, Ali; Reaser, Elizabeth, 1975-; Guinee, Tim; Smith, Lois, 1930-; Beatty, Ned; Heard, John, 1946-2017; Weaver, Will (Twentieth Century Fox Home Entertainment, 2007)
Inge is a feisty German mail-order bride who has come to Minnesota to marry Olaf, a young Norwegian immigrant farmer of few words. But in a post-WWI, anti-German climate, the local minister openly forbids the marriage. Inge and Olaf fall in love despite the town's disapproval. But when the town banker attempts to foreclose on the farm of his friend Frandsen, Olaf takes a stand--Container.